Tracing Histories of 'Black' Servants at Zwartkoppies Farm through Narratives (Journal of Decolonising Disciplines, 2021)
The purpose of this study was to trace histories of black individuals who were employed at Zwartkoppies Farm by the Marks family. I refer to them as servants as they spent their lives serving the Markers. Although it is apparent that Sammy Marks had both white and black servants, little is known about the black servants. Here I also deal with the issue of child labour and forced removals and discuss how the colonial and apartheid laws were enablers in violating black people' s human rights. I do so within the context of oral histories provided through interviews with descendants of 'servants' conducted between August 2018 and March 2020. This study is part of a masters research project entitled " Un-Silencing Histories of Black 'Servants'at Zwartkoppies Farm: A Transition from the Sammy Marks House to the Sammy Marks Museum", (2020).
Keywords: Sammy Marks, Zwartkoppies Farm, Servants, Oral History